Contracting for Reproductive Health Care : A Guide - Rosen, James E. (World Bank, Washington, DC, 2013)
Government contracting of private organizations is an increasingly common tool to meet the growing demand for quality reproductive health care in developing nations. This guide brings together information about such contracting experiences in a way to serve the practical needs of World Bank staff and their government counterparts in developing countries interested in trying contracting. Contracting is not a cure-all for ailing health systems, and there exists relatively little systematic evaluation of the contracting experience in developing countries. Still, many in the field recognize the potential of contracting as a powerful tool to improve reproductive health care. This guide touches on some of the reasons why governments go the contracting route. The guide is meant to be used during the development of new projects or during the supervision phase, and assumes that the reader: has identified population and reproductive health as an issue for the health sector in a particular country or region; already has decided to include a reproductive health component in the loan and wants to involve the private sector actively in the project; is considering opportunities for contracting out of reproductive health care; or is looking for ideas and models for contracting.